Implementation of Cambridge International Curriculum Biology and the Impact on Critical Thinking Skills of Students in Semesta High School - Najah, Suhaila Zakiya; Setiati, Ning (FMIPA UNNES, 2020)
Most of international schools in Indonesia are applying the Cambridge International Curriculum (CIC). This study aimed to explore the implementation of Biology Cambridge International Curriculum in Semesta High School and investigate its impact on students' critical thinking. This qualitative study employed a case study design and purposive sampling. A curriculum coordinator, a biology teacher, and 35 students were purposefully chosen to be a part of this study. Exploration of the implementation of CIC was performed using interview sessions, teaching-learning observations, and written materials. Open-ended questions were distributed to thirty-five students and interview 15 students to investigate the critical thinking of students. The findings of this study showed that Semesta High School provided quality amenities for students to support teaching-learning activities and students scored high in critical thinking tests. Major findings from this study concluded that Cambridge International Curriculum was highly implemented and well managed by Semesta High School and this implementation had a great influence on the critical thinking skills of students.